Interaction with the dental patient - Ustrell, Josep M. (2023)
Oral pathology must be successfully treated, but it depends on good planning from the beginning of the consultation and culminates with good functionality, aesthetics, and occlusal stability. In addition, it is essential to maintain this situation for as long as possible, an indeterminate time that will depend on the excellent performance of those who occupy the three vertices of an equilateral triangle: professional, team, and patient.